2010
DOI: 10.1371/journal.pgen.1001102
|View full text |Cite
|
Sign up to set email alerts
|

A Central Regulatory System Largely Controls Transcriptional Activation and Repression Responses to Phosphate Starvation in Arabidopsis

Abstract: Plants respond to different stresses by inducing or repressing transcription of partially overlapping sets of genes. In Arabidopsis, the PHR1 transcription factor (TF) has an important role in the control of phosphate (Pi) starvation stress responses. Using transcriptomic analysis of Pi starvation in phr1, and phr1 phr1-like (phl1) mutants and in wild type plants, we show that PHR1 in conjunction with PHL1 controls most transcriptional activation and repression responses to phosphate starvation, regardless of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
803
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 631 publications
(876 citation statements)
references
References 70 publications
43
803
0
2
Order By: Relevance
“…Since most regulated genes that respond to Pi starvation are under the control of the Myb transcription factor PHR1 and its close homolog PHL1 Bustos et al, 2010;Thibaud et al, 2010;Pant et al, 2015;Sun et al, 2016), we examined the role of these factors in PPsPase1 and PECP1 induction, including MGD3 as a control. By comparing gene induction levels using RT-qPCR in the wild type and phr1 phl1 double mutants , we observed that only a residual induction remained for these three genes in phr1 phl1 (Fig.…”
Section: Ppspase1 and Pecp1 Are Dynamic Markers Of Pi Starvationmentioning
confidence: 99%
See 1 more Smart Citation
“…Since most regulated genes that respond to Pi starvation are under the control of the Myb transcription factor PHR1 and its close homolog PHL1 Bustos et al, 2010;Thibaud et al, 2010;Pant et al, 2015;Sun et al, 2016), we examined the role of these factors in PPsPase1 and PECP1 induction, including MGD3 as a control. By comparing gene induction levels using RT-qPCR in the wild type and phr1 phl1 double mutants , we observed that only a residual induction remained for these three genes in phr1 phl1 (Fig.…”
Section: Ppspase1 and Pecp1 Are Dynamic Markers Of Pi Starvationmentioning
confidence: 99%
“…The fugu5-1 through -3 mutants as well as fugu5-1 PromAVP1:IPP1 #8-3 were previously described (Ferjani et al, 2011). The phr1 phl1 double mutant was also previously described (González et al, 2005;Bustos et al, 2010) …”
Section: Plant Materials and Transformationmentioning
confidence: 99%
“…In Arabidopsis, the direct targets of PHR1 are greatly enriched in P1BS-containing Pi starvation-induced genes (Bustos et al 2010). Therefore, PHR1 is maybe upregulated in late stages of −P stress via a P1BS cis-acting element.…”
Section: Promoter Analysis and Alternative Splicing Isoforms Of Respomentioning
confidence: 99%
“…Some transcripts may be regulated through the release from repression of PHO2/ UBC24 or regulated by other factors such as PHL1. Both PHR1 and PHL1 were found to be partially redundant and have a central role in the control of physiological and molecular responses to -P stress (Bustos et al 2010).…”
Section: Promoter Analysis and Alternative Splicing Isoforms Of Respomentioning
confidence: 99%
“…A number of transcription factors including the master regulator PHOSPHATE RESPONSE 1 (PHR1), and several members of the MYB and WRKY families of transcription factors have been shown to regulate the transcriptional activation of lowphosphate responsive genes and their corresponding binding sites P1BS, MBS and the W-box, respectively, act as cis-acting elements that mediate Pi starvation-responsive expression. [15][16][17][18][19][20] A search for these cis-acting motifs in Pi-methDEGs showed that 39 of these genes contained P1BS motifs, that present the palindromic 8 base pair sequence (GNATATNC) where PHR1 binds to DNA as a dimer, 15 93 genes had W-box elements which are the cognate binding sites of WRKY transcription factors, which have been characterized as key regulators of several processes in plants, including some members of this family which are specifically involved in the response to low Pi conditions, 17,19,21,22 and 80 genes contained MYB transcription factors Binding sites (MBS) (Fig. 1B).…”
Section: Differential Methylation Nearby Pi Responsive Motif Sequencementioning
confidence: 99%